CARTA DA TERRA COMO MATERIAL DIDÁTICO ESTRATÉGICO - Marilaine Bittencourt Mendes (TRF2, 2018)
The school is a collective and democratic space that needs to work values, as well as disciplinary contents, with children and young people in relation to citizenship and environmental awareness. Thus, several documents and books are indicated and adopted in the school as materials that aim to guide values. In this study, we will argue about the importance of working with the Carta da Terra, a document approved by UNESCO in Paris in March 2000, as a strategic tool to help children, from the initial series , understand the complexity of planet Earth and that can value the collective, citizenship and human solidarity.